Foyle's war. Set 6 [videorecording (DVD)] - Silberston, Jeremy; Foster, Giles; Kitchen, Michael, 1948-; Howell, Anthony, 1971-; Weeks, Honeysuckle, 1979-; Ovenden, Julian; Farrell, Nicholas; Redgrave, Corin (Distributed by Acorn Media, 2010)
Detective Chief Superintendant Christopher Foyle is a police investigator in the British coastal community of Hastings. In the immediate aftermath of World War II, Foyle finds his longed-for retirement interrupted by cases involving international intrigue, military racism, and an accused traitor all too willing to go to the gallows.